PENGEMBANGAN FITOREMEDIASI UNTUK MENINGKATKAN KUALITAS AIR LIMBAH HASIL PENGOLAHAN INSTALASI PENGOLAHAN AIR LIMBAH SUWUNG - Mahendra Dewi, N.L.P; Mahendra, Made Sudiana; Suyasa, I.W. Budiarsa (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2014)
Growing population and tourism activity in Bali Island increases quantity of waste water and resulting in degradation of sanitation quality, especially in the growth centre such as Kuta, Denpasar and Sanur areas. Suwung Waste Water Treatment Plant is one of facility available for domestic waste water in Bali. It needs improved treatment to process domestic waste water before it releases to the environment. Phytoremediation is one of treatment that use plant to coorporate with microorganisms in medium to transform contaminants becoming harmless. This research was conducted from June – August 2012 in Suwung Wastewater Treatment Plant using Taro plant and media form of pebbles and small natural stone. Acclimatized plant was prepared to make sure it can be ascertained and able to grow in tubs processing. Samples were taken 7 times in 24 hours, aiming to know effectiveness of phytoremediation system and to determine the most optimal detention time to reduce concentration of BOD, COD and Amonia. The result showed that treatment with phytoremediation system was effective for the reduction of BOD value with the highest effectiveness value of 84.29%, COD obtained the highest effectiveness value of 78.19% and ammonia got highest effectiveness value of 83.12%. Calculation of most optimal detention time for waste water was 6 hours for BOD, while for COD was obtained after 8 hours and 10 minutes and ammonia was obtained after 8 hours and 9 minutes. Comparison of result of waste water quality with waste water quality standard according to Bali Governor Act Number 8, year 2007, BOD and COD concentration complied the quality standard but for ammonia parameter was above waste water quality standard.
Keywords: Phytoremediation, effectiveness and detention time, waste water quality